Immunogenicity and safety of a novel ten-valent pneumococcal conjugate vaccine in healthy infants in The Gambia: a phase 3, randomised, double-blind, non-inferiority trial. Issue 6 (June 2021) - Clarke, Ed; Bashorun, Adedapo; Adigweme, Ikechukwu; Badjie Hydara, Mariama; Umesi, Ama; Futa, Ahmed; Ochoge, Magnus; Obayemi, Dolapo; Edem, Bassey; Saidy-Jah, Ebrima; Onwuchekwa, Chukwuemeka; Dhere, Rajeev; et al.
Summary: Background: An affordable pneumococcal conjugate vaccine (PCV) is needed to ensure sustainable access in low-income and middle-income countries. This trial examined the immunogenicity and safety of a novel ten-valent PCV (SIIPL-PCV) containing serotypes 1, 5, 6A, 6B, 7F, 9V, 14, 19A, 19F, and 23F compared with the pneumococcal polysaccharide protein D-conjugate vaccine (PHiD-CV; Synflorix; GlaxoSmithKline; Brentford, UK). Methods: In this single-centre, randomised, double-blind, phase 3, non-inferiority trial in The Gambia, healthy, PCV-naive infants aged 6–8 weeks were enrolled and assigned using permuted block randomisation to receive one of three lots of SIIPL-PCV or to PHiD-CV in a ratio of 2:2:2:3. Parents and all staff assessing study outcomes were masked to group assignment. Vaccines (0·5 mL SIIPL-PCV or 0·5 mL PHiD-CV) were administered at ages 6, 10, and 14 weeks by intramuscular injection. Primary immunogenicity outcomes, measured at age 18 weeks, were serotype-specific IgG geometric mean concentrations (GMCs) and seroresponse rates (IgG ≥ 0·35 μg/mL). Lot-to-lot equivalence (objective 1) was shown if the upper and lower bounds of the two-sided 95% CI around the GMC ratio for each pairwise lot-to-lot comparison was between the 0·5 and 2·0 equivalence margins for all ten serotypes. The immunogenicity of SIIPL-PCV was defined as being non-inferior to that of PHiD-CV (objective 2) if, for at least seven of the ten serotypes in SIIPL-PCV, the lower bound of the 97·5% CI for the GMC ratio was greater than 0·5, or the lower bound of the 97·5% CI for differences in seroresponse rate was greater than −10%. The GMC and seroresponse rates to serotypes 6A and 19A, which are not in PHiD-CV, were compared with those of the serotype in PHiD-CV that had the lowest seroresponse rate. Non-inferiority of the immune responses to antigens in the co-administered Expanded Programme on Immunization (EPI) vaccines (objective 3) was declared if the lower bound of the 95% CI for the difference between SIIPL-PCV and PHiD-CV in seroresponse rates, or GMC ratios for pertussis antigens, was greater than −10% (or 0·5 for pertussis antigens) for all vaccine antigens. Safety data were assessed according to treatment received at the first visit in infants who received at least one dose of study vaccine and for whom at least some post-vaccination safety data were available. The primary immunogenicity analysis was in the per-protocol immunogenicity population, which included infants who received all study vaccines and had immunogenicity measurements after vaccination and no major protocol deviations. This trial is registered at ClinicalTrials.gov (NCT03197376 ). Findings: Between June 21, 2017, and Jan 29, 2018, 2250 infants were enrolled and randomly assigned to receive SIIPL-PCV (n=1503; 502 to lot 1, 501 to lot 2, and 500 to lot 3) or PHiD-CV (n=747). 1458 (97·0%) infants assigned to SIIPL-PCV and 724 (96·9%) assigned to PHiD-CV were included in the per-protocol primary immunogenicity analysis. Lot-to-lot equivalence was shown, with the lowest lower bound of the 95% CI for the GMC ratio being 0·52 (for serotype 6B in lot 2 vs lot 3) and the highest upper bound being 1·69 (for serotype 6B in lot 1 vs lot 2). SIIPL-PCV was non-inferior to PHiD-CV in terms of immunogenicity: the lower bound of the 97·5% CI for the GMC ratio was greater than 0·5 (the lowest being 0·67 for serotype 19F) and the lower bound of the 97·5% CI for the difference in seroresponse rate was greater than −10% (the lowest being −2·2% for serotype 6B) for all ten serotypes in SIIPL-PCV. The lowest seroresponse rate after PHiD-CV was to serotype 6B (76·7% [95% CI 73·4–79·7]). This serotype was therefore used for the comparisons with serotype 6A and 19A in SIIPL-PCV. Non-inferiority of immune responses to the EPI vaccines after co-administration with SIIPL-PCV compared with after co-administration with PHiD-CV was shown for all vaccine antigens included in the primary series. The lowest lower bound of the 95% CI for the difference in seroresponse rates was −7·1% for rotavirus antibody and for the GMC ratio for pertussis antigens was 0·62 for anti-pertussis toxoid. 1131 (75·2%) of 1503 infants in the SIIPL-PCV group and 572 (76·6%) of 747 in the PHiD-CV group had at least one unsolicited adverse event. 36 (2·4%) participants in the SIIPL-PCV group and 18 (2·4%) in the PHiD-CV group had a serious adverse event; none were considered related to vaccination. In infants who were selected to have solicited adverse events recorded, injection-site induration after primary vaccinations occurred in 27 (4·9%) of 751 infants who received SIIPL-PCV versus 34 (9·4%) of 364 who received PHiD-CV (p=0·0032). There were no other notable differences in the safety profiles of the two vaccines. One infant in the SIIPL-PCV group and two in the PHiD-CV group died during the study. The deaths were not considered to be related to study vaccination or study participation. Interpretation: The immunogenicity of SIIPL-PCV was non-inferior to that of PHiD-CV, for which efficacy and effectiveness data against pneumococcal disease are available. The vaccine is safe and can be co-administered with routine EPI vaccines. The data generated in this trial have supported the licensure and pre-qualification of SIIPL-PCV, making the vaccine available for introduction into national immunisation programmes. Generating post-implementation data confirming vaccine impact remains important. Funding: Bill & Melinda Gates Foundation.